Overtime in minimizing construction delay - Saari, Syahmi (2014)
One of the significant problems in construction industry is delay. Construction projects frequently suffer delays and completed later than agreed time? Amongst various efforts, overtime has frequently become the planned schedule from the onset of a project to overcome delay in project. This study aims to analyse the effectiveness of overtime work in addressing problem of delay in construction project. The study identified that excavation and concreting work required the overtime work. Based on the study, overtime can be used to minimize the construction delay but overtime can be efficient way to minimizing delay by application of some methods of managing overtime in the project management. The most efficient methods can be adopt in the project are time management and scheduling management.